Optimum Pricing as Applied to Telephone Service - Hazlewood, Arthur (Review of Economic Studies, 1950)
Journal Article Optimum Pricing as Applied to Telephone Service Get access Arthur Hazlewood Arthur Hazlewood Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 18, Issue 2, 1950, Pages 67–78, https://doi.org/10.2307/2295794 Published: 01 April 1950